(untitled) - Prof. em. Dr Dr h.c. Herbert Haag, M.S. und Martin Holzweg (International Journal of Physical Education, 2019)
This magazine contains analyses and assessments of sports literature, published in both English and German, which encompasses the entire field of sports educational theory.The magazine represents a unique publication. As befitting scientific research and results, it contains all information about sports educational theory as a theoretical field of sports science. With this magazine, the reader can stay informed of new scientific literature and information.